GAMBARAN KETIDAK LENGKAPAN PENGISIAN FORMULIR RESUME MEDIS PASIEN RAWAT INAP DI RSUD X - Zahra Nur Afifah (LPPMK STIKES Widyagama Husada, 2021)
Preliminary: A medical resume is a summary of medical service activities provided by health workers, especially doctors during the treatment period until the patient is discharged either in good health or in death. Incomplete filling of medical resumes can be caused by negligence of officers or lack of understanding of the importance of completing patient data. This research is a descriptive research with a qualitative approach. In this study there were 4 medical recorder and 50 medical resume form. Method: The sampling technique used is the total sample. The data analysis used is descriptive data analysis. Results: Based on the results of the study, the incomplete medical resume form for inpatients in 2021 with a sample of 50 medical resume forms, the average percentage of medical resume completeness was 66.7%, while the incomplete medical resume was 33.3% of the 50 samples of medical resume forms. The highest percentage of incompleteness is the doctor's signature (52%). And the highest percentage of completeness is no medical record (76%). The problem that usually arises is that there are still many incomplete components of a medical resume. Conclusion: to overcome the problem usually requires more optimal socialization and collaboration between doctors and medical recorders, to further improve health services regarding the completeness of filling out medical record documents in order to improve the quality of health services, and the head of medical records needs to hold meetings or directives to the unit concerned so that the resume is filled out. can be carried out properly. Keywords: Incompleteness; inpatien; Medical Resume.